Book Notes [66, Fall 2010] - Finkel, Alvin (Labour/Le Travail, 2010)
The article briefly reviews "Exploring the Dimensions of Self-Sufficiency for New Brunswick," edited by Michael Boudreau, Peter G. Toner, and Tony Tremblay; "The State of Working America 2008/2009," by Lawrence Mishel, Jared Bernstein, and Heidi Shierholz,; "And They Were Wonderful Teachers: Florida’s Purge of Gay and Lesbian Teachers," by Karen L. Graves; "Agitate! Educate! Organize! American Labour Posters," by Lincoln Cushing and Timothy W. Drescher; "Hunger: A Modern History," by James Vernon; "Organising History: A Centenary of SIPTU [Services, Industrial, and Professional Trade Union of Ireland], 1909–2009; "by Frances Devine; "Revenge of the Domestic: Women, the Family, and Communism in the German Democratic Republic," by Donna Harsch; and "Logics of Empowerment: Development, Gender, and Government in Neoliberal India," by Aradhana Sharma.